Study of Nanoporous Carbon Fabrics for Rechargeable Energy Storage Capacitors. (31st May 2017) - Karabanov, Sergey M.; Litvinov, Vladimir G.; Karabanov, Andrey S.
ABSTRACT: The present paper examines nanoporous material – carbon fabrics, which is used as electrodes in rechargeable energy storage capacitors (ultracapacitors). The fabrics structure, impurities composition, the influence of impurity types on ultracapacitor characteristics and the influence of thermal treatments on the impurities concentration are studied. The analysis of the ultracapacitor equivalent circuit with the studied material is made and the capacitor charge-discharge characteristics are investigated. The performed studies resulted in determination of the investigated carbon material structure, determination of impurities composition of carbon material and change of impurities content depending on thermal treatment in vacuum. The optimum temperature range for treatment in vacuum is established. The equivalent circuit of the ultracapacitor is analyzed and its charge-discharge characteristics are investigated. The chosen equivalent circuit makes it possible to estimate the influence of pores different size on the ultracapacitor charge-discharge characteristics that is important for its application in energy storage devices.